Pengawasan Terhadap Realisasi Anggaran Dengan Konsep Good Governance Dalam Mencegah Praktik Korupsi Di Dinas Pekerjaan Umum Dan Penataan Ruang Kota Palembang - Imam Suroso; Masnoni; Hilwa Anggraini; Nelly; Roy Saleh (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2020)
The results of this study indicate that the budget flow and process in budget planning starts from conducting an investigation field survey, after conducting a survey. After that DPA was published, we switched to the physical implementation of the work, including planning, design and so on. The concept of good governance in supervising the realization of the government's budget is responsible for optimizing the relationship between inputs and outputs. For example,in the Public Works and Spatial Planning Office of Palembang City. The input in the form of a budget can still be seen in its performance. Control is focused on how to make use of minimal inputs, with terms and quality standards set at the desired time and quantity.